Effects of sex and the common ADRB1 389 genetic polymorphism on the hemodynamic response to dobutamine. Issue 11 (November 2015) - Yogev, Dotan; Basheer, Maamoun; Blotnick, Simcha; Caraco, Yoseph; Muszkat, Mordechai
Abstract : Introduction: The ADRB1 389 polymorphism affects responses to the β-1 adrenergic receptor (β1 AR) agonist in vitro . Previous studies on its effect on the response to dobutamine stress echocardiography were conflicting. In addition, sex differences in the response to dobutamine have been suggested. The aim of this study was to determine whether the ADRB1 389 polymorphism affects the hemodynamic response to dobutamine in healthy individuals including men and women. Participants and methods: Healthy individuals were recruited according to their ADRB1 49 and 389 genotypes [15 Arg389Arg, 10 Gly389Arg, and 10 Gly389Gly individuals, (all Ser49Ser), 21 men and 14 women]. Dobutamine was infused at 2, 4, and 6 mcg/kg/min. Standardized exercise was performed during the last minute of each infusion. Results: Resting heart rate (HR) response to 6 mcg/kg/min dobutamine (ΔHR) was 4.7-fold larger in Arg389Arg than in Gly389Gly [(mean±SD) 12.95±6.99, 2.75±1.65 bpm, respectively, P ANOVA =0.012]. Renin response to dobutamine (ΔRenin) was 3.9-fold greater in Arg389Arg than in Gly389Gly ( P ANOVA =0.032). Among Arg389Gly heterozygotes, ΔHR and ΔRenin were not significantly different from either homozygote group. In multivariate analysis for ΔHR variance, significant contributions were observed for genotype ( P =0.011), baseline HR ( P =0.011), and borderline effect for sex ( P =0.049). Conclusion: In healthy individuals, HR and renin responses to dobutamine were more than three-fold greater among ADRB1 Arg389 compared with Gly389 homozygotes. Future studies on the effect of the ADRB1 389 polymorphism on dobutamine stress echocardiography should compare Arg389 and Gly389 homozygotes.